Leaders who transform society what drives them and why we are attracted - Popper, Micha (Westpor Praeger Publishers, 2005)
In this wide-ranging historical exploration of transformationnal leadership, Popper examines why followers are influenced by leaders and what psychological dynamics exist between leaders and their subordinates, and in the process, redefines the phenomenon of leadership. Exploring the emotional connections that bind charismatic leaders and those who support them, he contends that this multifaceted relationship is based on reciprocal need. By focusing on prominent figures throughout history who have altered the lives of their followers in profound ways, Popper shows how these leaders reinvented and disseminated value systems, for good (e.g., Nelson Mandela) and for the ill (e.g., Hitler). Whether the influence of a charismatic leader is destructive and negative or constructive and positively transformative, this intriguing work argues that the reciprocal process that takes place between leader and follower, and key formative events in the lives of leaders, are surprisingly similar.
ncludes bibliographical references (p. 120-146)
Keywords: Leadership